Designing Dynamic Capability of Uang Kepeng Craftsmen in Kamasan, Klungkung, Bali - Kusumawijaya Ida Ketut; Partiwi Dwi Astuti; Wartana I Made Hedy; Adi I Ketut Yudana (International Journal Of Community Service, 2026)
This community service initiative addresses the urgent need to enhance the sustainability and adaptive capacity of Uang Kepeng craftsmen in Kamasan Village, Klungkung, Bali, a culturally rich craftsmen community facing significant challenges in modernizing traditional practices amid dynamic market shifts. The objective of the program was to design and implement a dynamic capability framework tailored to the specific conditions of these small and medium-sized enterprises rooted in heritage craftsmanship. The community service was conducted using a participatory pction research approach, involving 11 active craftsmen. The methodology comprised three key phases: an initial pre-test to assess baseline knowledge of dynamic capabilities, participatory capacity-building workshops focused on idea generation, promotion, and realization, and a post-test evaluation to assess measurable improvement. These stages were complemented by continuous monitoring and feedback mechanisms to ensure responsiveness and relevance throughout the intervention. The results demonstrate a significant improvement across all dimensions of dynamic capability, with average scores rising from a pre-test baseline to a post-test mean. Craftsmen showed marked advancements in innovation orientation, strategic flexibility, knowledge absorption, and cultural adaptation. The program successfully bridged the gap between traditional skill sets and the strategic agility required to thrive in today’s creative economy. Discussions revealed both the potential of these craftsmen to evolve through targeted empowerment and the challenges posed by limited digital literacy, generational divides, and operational informality. In conclusion, this community service program provided evidence of the effectiveness of dynamic capability interventions in traditional, low-digital economies. The initiative not only empowered the local craftsmen community to adapt and innovate but also contributed to the theoretical application of dynamic capabilities in socio-cultural contexts. The findings highlight the importance of integrating culturally grounded methods with strategic development to ensure sustainable community transformation.